Pengaruh Faktor–Faktor Pembentuk Budaya K3 pada Kinerja K3 Pekerja Proyek Kegiatan Drilling Rig di PT X Lapangan Y - Heri Setiawan; Soehatman Ramli; Syahfirin Syahfirin (Syntax Literate, 2023)
The drilling rig construction project has the characteristic that its workers experience the impact of limited time and budget pressures in the planning and execution of activities, most of which are carried out by skilled human workers who are temporary in nature who migrate from one place to another and are heavily influenced by weather conditions and The surrounding environment is a few special characteristics that distinguish drilling rig activity projects in well drilling from construction projects in other industries. The forming factors of OSH culture have an effect on improving the OSH performance of workers on drilling rig activity projects and OSH culture at PT X. This research was conducted to identify and analyze the factors forming OSH culture which influence the OSH performance of workers, especially on drilling rig activity projects, as well as analyzing the influence of the factors forming the OSH culture on the OSH performance of the drilling rig activity project workers. The independent variables: Worker Commitment to K3 (X1), Compliance with K3 Regulations and Procedures (X2), Worker Communication in K3 (X3), Worker Competence in K3 (X4), Worker Involvement in K3 (X5), Worker Environment (X6), While the dependent is the K3 Performance of Drilling Activity Project Workers (Y). Data analysis in this study used descriptive statistical analysis and multivariate analysis with the Smart Partial Least Square 3 (SmartPLS 3) approach. The results of the analysis of the behavior of the respondents were male, mostly aged 36-45 years, had a Bachelor's degree, and had worked for more than 6 months and the results of the analysis of the respondents' perceptions of each variable obtained an average value calculated between 4.18 – 4.34. The results of the Smart Partial Least Square 3 analysis show that the independent variables consisting of workers' commitment to OHS (X1), Compliance with K3 regulations and procedures (X2), and Worker Involvement in OHS (X5) have a significant and positive effect on the dependent variable OHS Performance of Project Workers Drilling Rig Activities (Y).